Genocide denials and the law - Hennebel, Ludovic; Hochmann, Thomas (New York ; Oxford : Oxford University Press, 2011)
In 'Genocide Denials and the Law', Ludovic Hennebel and Thomas Hochmann offer a thorough study of the relationship between law and genocide denial from the perspectives of specialists from six countries. This topic provokes strong international reactions involving emotion caused by denial along with concerns about freedom of speech.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Genocide; Criminal liability (International law); Holocaust denial